Myasthenia gravis and nutrition - Uçak, Merve Nur; Arıtıcı Çolak, Gözde (Frontiers in Nutrition, 2025)
Myasthenia gravis is an autoimmune neurological disease characterized by a disorder of nerve transmission at the neuromuscular junction. In this disease, antibodies attack acetylcholine receptors and their associated molecules, disrupting nerve transmission and impairing normal muscle contraction. Myasthenia gravis is diagnosed through physiological and neurological examinations, blood antibody tests, and electronic methods. Various approaches are used for symptom management, including immunosuppressive drugs, acetylcholinesterase inhibitors, and thymectomy. Previous literature has focused primarily on symptoms and medical treatment. However, resources related to nutrition and Myasthenia gravis are limited. This study bridges this gap by examining the effects of different nutritional interventions on the disease and the importance of nutrition in the treatment process.